PDE5A Polymorphisms Influence on Sildenafil Treatment Success. Issue 7 (1st July 2016) - Marchal-Escalona, Cristobal; Herrera-Imbroda, Bernardo; Clemente-Postigo, Mercedes; Alcaide-Torres, Juan; Quiñonero, Antonio; Marchal, Marta; Queipo-Ortuño, María Isabel; Aragón, Isabel María; Martín-Morales, Antonio; Lara, María Fernanda; Cardona, Fernando
ABSTRACT: Introduction: Diabetes and cardiovascular disease are risk factors for erectile dysfunction (ED). Selective inhibitors of the type 5 phosphodiesterase are the first option for treating ED. However, it is unknown why there are patients with low response to this treatment. Polymorphisms in the PDE5A gene may influence the response to PDE5 inhibitors treatment. Aim: The aim of this study is to analyze the relationship between PDE5A polymorphisms, diabetes, and the efficacy of sildenafil treatment. Methods: A Spanish prospective cohort of 170 Caucasian male patients diagnosed with ED and ischemic heart disease treated with angioplasty was studied. Main outcome measures: ED was evaluated according to the 5-item version of the International Index for Erectile Function before and after treatment with sildenafil 50 mg. The gene sequence of the PDE5A gene was analyzed for the presence of rs12646525 and rs3806808 polymorphisms. Glucose and glycosylated hemoglobin levels were measured in blood serum samples. The relationship between treatment response, genotype, and glycemic status was analyzed. Results: Patients with G-allele of rs3806808 polymorphism showed a worse response to the treatment compared to TT-homozygote patients. Nondiabetic G-allele carriers showed a worse treatment response than TT-homozygotes patients. These differences were not seen in diabetic patients. There were no significant differences in treatment response according to the rs12646525 polymorphism in total population or according to the glycemic status. Logistic regression analysis showed that nondiabetic carriers of the major allele of both the rs12646525 and rs3806808 polymorphism had a significantly higher likelihood to respond to the treatment than diabetic patients carriers of the minor allele ( P < .05). Conclusion: The response to sildenafil treatment depends on polymorphisms in the PDE5A gene and the glycemic status of the patients.